Problematika Pemberian Otonomi Khusus Provinsi Daerah Khusus Jakarta Yang Hanya Berada Pada Tingkat Provinsi - Lubis, Alfi Syahri; Saputro, Bayu; Wibowo, Renaldy Wijaksana; Al-Qindi, M. Fariz (UI Scholars Hub, 2024)
On April 25, 2024, the legislators officially passed Law Number 2 of 2024 concerning the Special Region of Jakarta Province. One of the articles that is still maintained in the a quo law is the matter that regulates the granting of autonomy only at the provincial level. This certainly has its own characteristics compared to the autonomy given to other regions that get autonomy up to the district / city level. The results of the study suggest several things, first, the reason the government maintains the specificity of the Special Region of Jakarta only at the provincial level is due to the history of government, the effectiveness and efficiency of governance, and the urban character of Jakarta. As a result of the specificity that is only at the provincial level, the Special Region of Jakarta does not have a Regency / City Regional House of Representatives. The existence of the district/city legislative council is replaced by the city council/district council whose duties and functions are very different. The absence of a district/city legislative council has led to the loss of three important functions of local government administration, namely the formation of district/city regulations, the budget function, and the supervisory function.